2018
DOI: 10.1055/s-0038-1642025
|View full text |Cite
|
Sign up to set email alerts
|

Tocolysis among Women with Preterm Birth: Associated Factors and Outcomes from a Multicenter Study in Brazil

Abstract: Tocolysis is favored in cases of earlier labor and also among those with less than 34 weeks of gestation, using preferably calcium channel blockers, with success in achieving increased corticosteroid use. Tocolysis, in general, was related to higher maternal and neonatal complication rates, which may be due to the baseline difference between cases at admission. However, these results should raise awareness to tocolysis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
1
0
4
Order By: Relevance
“…The history of preterm labor is another factor inducing preterm labor pain [10]. From this study, it was found that preterm labor history is not a factor relating to unsuccessful uterus contraction inhibition.…”
Section: Table 1 Baseline Maternal Characteristics Of Pregnant Women mentioning
confidence: 67%
“…The history of preterm labor is another factor inducing preterm labor pain [10]. From this study, it was found that preterm labor history is not a factor relating to unsuccessful uterus contraction inhibition.…”
Section: Table 1 Baseline Maternal Characteristics Of Pregnant Women mentioning
confidence: 67%
“…(Duarte et al, 2021). Alves et al, (2021) destaca que mulheres que apresentam mais de três partos possuem um risco maior de TPP e tal fato pode estar ligado à forma de implantação do óvulo fecundado na parede uterina (Dias et al, 2018). Essa informação vai de encontro com os resultados desse estudo, no qual 13 dos 20 recém-nascidos pré-termo vieram de mães multíparas, e dessas, 8 estavam, no mínimo, na terceira gestação.…”
Section: Discussionunclassified
“…Pontua-se, que a multiparidade é um dos fatores de risco mais importantes na história de parto prematuro prévio, e mulheres que apresentam mais de três partos possuem um risco maior que aquelas com dois ou menos partos, e isso pode estar ligado à forma de implantação do óvulo fecundado na parede uterina. 10 Nota-se, com relação à exposição ao tabagismo durante a gestação, que é possível que este atue como um indicador de risco para o nascimento prematuro. Aumentar-se-ia, pelo efeito acumulativo do tabagismo, o risco de nascimento prematuro ocasionado pelo TPP, o que não foi visualizado no estudo, pois o número de gestantes tabagistas foi baixo entre as gestantes entrevistadas.…”
Section: Discussionunclassified